Enteroparásitos en estudiantes de la Escuela Técnica Agropecuaria Robinsoniana “Caicara”, Caicara del Orinoco, municipio Cedeño, estado Bolívar, Venezuela - Devera Rodolfo; Blanco Ytalia; Requena Ixora; Tedesco Rosa María; Alvarado José; Alves Nellys; Belisario, Richard (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2010)
Abstract: To determine the prevalence of enteroparasites, 136 students attending the Escuela Técnica Agropecuaria Robinsoniana “Caicara”, Caicara del Orinoco, Cedeño Municipality, State of Bolivar, were assessed. A stool sample was collected for each student, which was analyzed by direct examination, Kato, Willis, spontaneous sedimentation and agar plate culture techniques. The prevalence of intestinal parasites was 89% (121/136). In all age groups, parasites were diagnosed (=3.873, f.d. =3p> 0.05). Both sexes were equally affected (p > 0.05). A total of 12 species of parasites and/or commensals were diagnosed. Protozoa were more prevalent (98.4%) than helminthes (30.0). Blastocystis hominis was the most prevalent intestinal parasite in 79.4%. In conclusion, results showed a high prevalence (89%) of intestinal parasitic infection in the population studied, with no predilection for sex or age, with prevalence for protozoa, particularly B. hominis. Sanitary and sanitation deficiencies could explain such high prevalence rates. Resumen: Para determinar la prevalencia de enteroparásitos, fueron evaluados 136 alumnos pertenecientes a la Escuela Técnica Agropecuaria Robinsoniana “Caicara”, Caicara del Orinoco, municipio Cedeño del estado Bolívar. De cada estudiante se obtuvo una muestra fecal la cual fue analizada mediante las técnicas de examen directo, Kato, Willis, sedimentación espontánea y cultivo en placa de agar. La prevalencia de parasitosis intestinales fue de 89% (121/136). En todos los grupos de edad se encontraron parásitos (= 3,873; g.l.= 3 p >0,05). Ambos sexos fueron afectados por igual (p>0,05). Se diagnosticaron 12 especies de parásitos y/o comensales intestinales. Los protozoarios fueron más prevalentes (98,4%) que los helmintos (30%). Blastocystis hominis fue el parásito intestinal más prevalente con 79,4%. En conclusión, se determinó una elevada prevalencia (89%) de enteroparásitos en la población estudiada, sin predilección por el sexo o la edad, con predominio de los protozoarios, en ...